1986
DOI: 10.1016/s0735-1097(86)80458-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of incomplete right bundle branch block: An epidemiologic study

Abstract: A cohort of 1,960 white men aged 40 to 56 years without initial apparent heart disease and with 11 years of annual rest electrocardiograms and 20 year mortality data was followed in the Chicago Western Electric Company Study. Incomplete right bundle branch block was found in 134 men (6.8%) at entry. During follow-up, 222 men developed such block, an incidence rate of 13.6%. Left axis deviation of -30 degrees or less was more frequent in men with than in those without incomplete block at entry (8.2 versus 2.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…The same is true for heart rates between 50 and 60 beats/min without conduction abnormalities. A study by Liao et al . showed an increased likelihood of development of a CRBBB when having an IRBBB.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for heart rates between 50 and 60 beats/min without conduction abnormalities. A study by Liao et al . showed an increased likelihood of development of a CRBBB when having an IRBBB.…”
Section: Discussionmentioning
confidence: 99%
“…In the early Seven Countries study report,3 however, neither right nor left bundle branch blocks were found to be predictive for CHD death, but this result was based on only two deaths. In the analysis of follow up data from the Chicago Western Electric Company study, Liao et al also found no increased risk of death from CHD and CVD in persons with incomplete right bundle branch block 12. In the Reykjavik study22 a significantly higher mortality from heart disease was found in men and women with right bundle branch block, but the significance of the association disappeared in the multivariate Cox regression analysis, mainly because of the confounding effect of underlying cardiovascular findings such as hypertension and raised blood glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Baltimore Longitudinal study of Aging (BLSA) has a biennial follow‐up (annually if subject >70 years old) over a 26‐year period . The Chicago Heart Association Detection Project had ECGs at baseline and every 5 years up to 19 years while the Chicago Western Electric Study had annual follow‐up ECGs . The Australian epidemiology study of Busselton had ECGs at baseline and after 13 years while a Belgian population study and another study of 1,000 aviators by Packard et al had ECGs at baseline and at 10 years.…”
mentioning
confidence: 99%